Monitoring heavy metal contamination levels and microbiological pollution in seawater of Agadir coastal zones - Bazzi, Illyass; Mouaden, Khadija El; Chaouay, Aicha; Addi, Abdelaziz Ait; Hamdani, Mohamed; Issami, Souad El; Hilali, Mustapha; Hammouti, Belkheir; Abbiche, Khalid; Salghi, Rachid (Universitas Pendidikan Indonesia, 2020)
The objective of this study was to monitor the bacteriological contamination of the seawater of the marine fisheries of the coastal Agadir, Morocco. The study was focused on the diagnosis on the pollution in heavy metals, such as cadmium, lead, and mercury in five zones: the port of Imi Ouaddar fish boarding (zone Z1), the old port of Agadir (zones Z2 and Z3), the port of Agadir Marina (zone Z4), and the estuary of Oued Souss (zone Z5). The analyses were done by testing physicochemical parameters (such as pH, temperature, dissolved oxygen, salinity and conductivity) as well as microbiological and atomic adsorption analyses. The experimental results showed that the values of the physicochemical parameters were almost the same in all zones, while the microbial conditions were different, in which this is due to the existence of heavy metals. The more heavy metal concentrations affected the condition of microbes in the sea water, confirmed by the number of Escherichia coli. This study demonstrated the importance of controlling concentration of heavy metals for better sustainability of environment.